Corn growth, yield and weed composition as influenced by different nitrogen rates and plant densities - Zahid, Obaidurahman; Ahmad Hamdani, Muhammad Saiful; Tanha, Jamal; Safi, Samiullah (Agri Bio Publisher, 2024)
Sufficient nitrogen application is the main factor in plant growth and yield development processes. Therefore, a field research was conducted during 2020 at Field 15, Faculty of Agriculture, Universiti Putra Malaysia in Serdang, Selangor, to quantify the effect of four nitrogen rates N1 (120 kg N/ha), N2 (140 kg N/ha), N3 (160 kg N/ha) and N4 (180 kg N/ha) and two planting densities D1 (75 x 20 cm) and D2 (65 x 20 cm) on growth and yield attributes of corn variety (GWG 888) and weed composition. The results showed that both factors (nitrogen rates and planting densities) significantly influenced corn growth, yield and weed composition. It was observed that N3 (160 kg N/ha) produced the maximum plant height, number of leaves, cob number, cob length and dry mater yield. The maximum number of the weed species and weed population were obtained with 180 kg N/ha. Higher plant density (65 x 20 cm) decreased plant height and leaf; however, it significantly enhanced dry matter yield. The findings suggested that the use of 160 kg N/ha was appropriate nitrogen rate at 75 x 20 cm, which improved corn growth and yield.